2015
DOI: 10.1097/qai.0000000000000459
|View full text |Cite
|
Sign up to set email alerts
|

Location of HIV Diagnosis Impacts Linkage to Medical Care

Abstract: We evaluated 1,359 adults newly diagnosed with HIV in Philadelphia in 2010-2011 to determine if diagnosis site (medical clinic, inpatient setting, counseling and testing center (CTC), correctional facility) impacted time to linkage to care (difference between date of diagnosis and first CD4/viral load). 1,093 patients (80%) linked to care: 86% diagnosed in medical clinics, 75% in inpatient settings, 62% in CTCs, and 44% in correctional facilities. Adjusting for other factors, diagnosis in inpatient settings, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 33 publications
(37 reference statements)
2
16
0
Order By: Relevance
“…9 The closest HIV clinic (IDP) for uninsured Atlanta metro area residents with a CD4 count <200 cells/lL is less than 2 miles from the hospital. The Fulton County Health Department, where uninsured patients with a CD4 count >200 cells/lL are generally referred for care, is located directly across the street from GMH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 The closest HIV clinic (IDP) for uninsured Atlanta metro area residents with a CD4 count <200 cells/lL is less than 2 miles from the hospital. The Fulton County Health Department, where uninsured patients with a CD4 count >200 cells/lL are generally referred for care, is located directly across the street from GMH.…”
Section: Discussionmentioning
confidence: 99%
“…9 HIV diagnosis and timely linkage to care remain a critical aspect of the test-andtreat approach for HIV prevention, yet successful linkage to care is not sufficient for effective broad-scale treatment as prevention. 10,11 At Grady Health System (GHS), we are uniquely situated to describe a full care continuum for patients who are newly diagnosed in the hospital.…”
Section: Introductionmentioning
confidence: 99%
“…These include transitions from correctional institutions to community-based care, inpatient to outpatient care, and pediatric/adolescent to adult clinics. A study evaluating 1,359 newly diagnosed HIV-infected patients found that, compared to medical clinics, diagnosis at correctional facilities, counseling and testing centers, and inpatient settings resulted in a 75%, 46%, and 33% decrease in the probability of linkage, respectively [45]. In a retrospective cohort study of 2,215 HIV-infected patients who were receiving ART at a Texas prison, only 30% filled their first ART prescription within 60 days after their release [46].…”
Section: Barriers and Facilitators To Retention And Adherencementioning
confidence: 99%
“…HIV status disclosure to family/relatives was significantly associated with linkage to care (AHR=2.64; 95% CI 2.05 to 3.39). In this same option, a study carried out by Yhia et al [12] in the USA (Philadelphia), demonstrated that diagnosis in inpatient settings, counseling and testing centers, and correctional facilities resulted in a 23% (AHR 0.77, 95% confidence interval 0.64-0.92), 46% (0.56, 0.42-0.72), and 75% (0.25, 0.18-0.35) decrease in the hazard of linkage to care compared to diagnosis in medical care clinics, respectively. Additionally, the hazard of not linking to care was greater for black patients (vs. white), persons with IDU as their HIV risk factor (vs. heterosexual), and those diagnosed in 2010 (vs. 2011).…”
Section: Discussionmentioning
confidence: 99%